Practical aspects of adoption cases consideration in juvenile courts of Kazakhstan - Mutubayeva, D.M. (Bulletin of the Karaganda University “Law Series”, 2019)
The article reveals the specifics and features of the consideration of adoption cases of Kazakh children in the juvenile court in line with the national legislation. Consideration of adoption cases was analyzed, including adoption not only by Kazakhstani citizens, but also by foreign citizens. The practice of application of the legislation following from marriage and family legal relations is considered.The article shows statistical data, the comparative analysis of the previous legislation with the current one. The increase in the number of children adopted entails the protection of the child rights and interests. Since the child interests are understood to mean proper family education, and the protection of the child interests means a lot for his future development, and how each of the parents will be able to provide the child with a favorable development. Adoption cases by juvenile courts follow the Constitution of the Republic of Kazakhstan, the code of the Republic of Kazakhstan «on marriage (matrimony) and the family». Social workers, psychologists, teachers participate in the case hearing. Overall, the current practice of the juvenile court with such cases brings a positive result. This approach shows that the state and society give priority to the family education of children, taking care of their development and well-being.